Quality of service in public higher education institution (HEI) facilities: a critical literature review - Hasbullah, Amilia; Wan Yusoff, Wan Zahari (Universiti Teknologi Malaysia, 2018)
This study presents an initial step for the development of a suitable approach to assess public higher education institution (HEI) facilities’ service quality. Nowadays, spirit of service excellence has become prominent within HEIs. In this sense, research focused on quality of service in public HEI context. This topic mostly discusses about service quality in programmes and processes in HEIs. Nevertheless, studies focusing on service quality, particularly in facilities, are still lacking. This justifies the development of an approach to assess quality of service in public HEI facilities.